Translation and cultural adaptation of the COVID-19 Yorkshire Rehabilitation Scale into German - Sperl, Lisa; Stamm, Tanja; Mosor, Erika; Ritschl, Valentin; Sivan, Manoj; Hoffmann, Kathryn; Gantschnig, Brigitte (Frontiers in Medicine, 2024)
Background: Experts estimate that in up to 10% of the infected, SARS-CoV-2 would cause persistent symptoms, activity limitations and reduced quality of life. Referred to as long COVID, these conditions might, in the future, specifically impact German-speaking countries due to their higher rates of unvaccinated people compared to other Western countries. Accurate measurement of symptom burden and its consequences is needed to manage conditions such as long COVID, and several tools have been developed to do so. However, no patient-reported instrument existed in the German language at the time of writing. Objective: This study, therefore, aimed to develop a German version of the COVID-19 Yorkshire Rehabilitation Screening Tool (C19-YRS). Methods: We conducted a translation and qualitative evaluation, including cultural adaptation, of the C19-YRS and assessed its face validity. After creating a preliminary version, 26 individuals (14 women [53%]) participated in cognitive interviews (January 2022 to March 2022). Using cognitive debriefing interviews, we ensured the content's comprehensibility. The matrix-framework method guided the qualitative data analysis. Results: Compared to the original English version, adaptations were necessary, resulting in changes to the introductory text, while the items for recording persistent symptoms were hardly changed.The German version of the C19-YRS is expected to support standardised long COVID care.We conducted a translation and qualitative evaluation, including cultural adaptation, of the C19-YRS into German and assessed its face validity.The COVID-19 Yorkshire Rehabilitation Screening Tool is a 22-item patient-reported outcome measure for assessing and monitoring long COVID symptoms and was the first long COVID-specific scale reported in the literature 18 . Considering psychometric properties, the English version of the C19-YRS showed good internal consistency, and scaling and targeting assumptions were satisfied 19 .